Effects of stabilizer ratio on the optical constants and optical dispersion parameters of ZnO nano-fiber thin films - Yahia, I. S.; Farag, A. A. M.; Cavas, M.; Yakuphanoğlu, Fahrettin (Academic Press Ltd- Elsevier Science Ltd, 2013)
The effects of the molar ratio of stabilizer on structural and optical properties of ZnO nanocrystalline films have been investigated. The AFM images indicate that the ZnO films are formed from the nano-fibers. The optical transmittance spectrum indicates the average transmittance higher than 85% at higher wavelengths. In UV spectrum, the transmittance increases with followed by a slight decay within visible range. The results of the absorption coefficient were analyzed in order to determine the optical band gap of the films. The optical constants (refractive index and absorption index) of the thin films were determined. Moreover, the dispersion parameters such as dispersion energy, oscillator energy, dielectric constants and dissipation factor were determined. The most significant result of the present study is to indicate that the molar ratios of MEA to ZnAc in the prepared ZnO nanocrystalline films have a little effect on the optical band gap but can be used to modify the optical dispersion parameters of the prepared ZnO nanocrystalline thin films. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: ZnO nano-crystalline; Sol-Gel; Non-vacuum spin coating; Optical dispersion parameters; Dielectric constants; Optical conductivity